Associations of maternal gestational diabetes mellitus with alterations in cardiovascular system in early childhood. Issue 6 (7th June 2022) - Li, Zhuoyan; Wu, Yujian; Du, Bowen; Yu, Xiaodan; Wang, Hualing; Niu, Yiwei; Wang, Jian; Chen, Sun; Sun, Kun
Abstract: Aims: The association of maternal gestational diabetes mellitus (GDM) with childhood cardiovascular alterations is not well established. This study aims to test the hypothesis that prenatal exposure to GDM is associated with vascular and cardiac alterations in early childhood. Methods: In a population‐based prospective cohort among 1094 mothers and their offspring, GDM was diagnosed according to the International Association of Diabetes and Pregnancy Study Groups criteria. Childhood blood pressure (BP) measurement, echocardiography and vascular ultrasound were performed using standardised methods at 4 years old. The associations between maternal GDM and childhood cardiovascular outcomes were modelled using linear regression and binary logistic regression. Mediation analysis was conducted to test the potential mediators. Results: Maternal GDM was associated with higher systolic BP (SBP; β, 1.20; [0.11, 2.28]), lower left ventricular end‐diastolic diameter (LVEDD; β, −0.36; [−0.71, −0.01]), lower end‐diastolic volume (EDV; β, −1.42; [−2.71, −0.13]) and increased risk of high blood pressure (HBP, OR = 1.522; 95% CI, 1.023 to 2.264) in offspring at the age of 4 years. After stratification by sex, the association remained strong only in male offspring (SBP: β, 1.94; [0.37, 3.51]; LVEDD: β, −0.60; [−1.09, −0.12]; EDV: β, −2.09; [−3.86, −0.31]; HBP: OR = 1.797; 95% CI, 1.063 to 3.037) and was independent of maternal and child characteristics. However, carotid intima‐media thickness (cIMT) was not associated with maternal GDM. Mediation analysis showed that the effects on childhood cardiovascular alterations were attributable mostly to the direct effects of maternal GDM. Conclusions: Our results provide evidence that maternal GDM is associated with offspring cardiovascular adaptations at preschool age. Further studies are needed to replicate our results and the long‐term effect of these adaptations on later cardiovascular risks needs further investigation.